Distribution of ocular biometry in young Chinese eyes: The Anyang University Students Eye Study. Issue 6 (16th December 2020) - Sun, Yunyun; Wei, Shifei; Li, Shiming; Cao, Kai; Hu, Jianping; Yang, Xiaohui; Lin, Caixia; An, Wenzai; Guo, Jiyuan; Li, He; Fu, Jing; Wang, Ningli
Abstract: Purpose: To investigate the distribution of ocular biometric parameters and its association to refraction in university students in central China. Methods: Ocular biometric parameters including axial length (AL), central corneal thickness (CCT), keratometry power (K), anterior chamber depth (AQD) and lens thickness (LT) were measured by an optical biometry in a cohort of university students. Corneal radius of curvature (CR), lens position (LP), lens power (PBennett ), vitreous chamber depth (VCD) and AL to corneal radius ratio (AL/CR) were calculated. Cycloplegic refraction was measured using an autorefractor. Results: A total of 7650 undergraduate students participated in this study, with a mean age of 20.0 ± 1.4 years. The following ocular biometric parameters were measured: AL (24.78 ± 1.21 mm), CCT (539.83 ± 33.03  μ m), AQD (3.23 ± 0.25 mm), LT (3.47 ± 0.18 mm), CR (7.79 ± 0.27 mm), LP (4.97 ± 0.23 mm), VCD (17.55 ± 1.15 mm), PBennett (25.00 ± 1.07 dioptres) and AL/CR (3.18 ± 0.15). Male subjects were found to have longer AL, thicker CCT, flatter CR, thinner lens, deeper AQD and VCD than female ones. Myopic subjects were found to have longer AL, thinner CCT, steeper CR, thinner and posterior lens, deeper AQD and VCD, lower PBennett and larger AL/CR than emmetropes and hyperopes. Spherical equivalent (SE) showed a negative correlation with AL/CR ( r  = −0.914), AL ( r  = −0.755) and VCD ( r  = −0.751). Conclusions: This study provided a range of reference values for the main ocular biometric parameters in young adults and reported their distributions based on gender and refractive status. Our study indicates that SE has a strong correlation with AL/CR ratio, AL and VCD.